Evaluating the integrity of polymersomes by FRET for optimization of the lyophilization parameters. (8th November 2022) - Liu, Yuan; Hu, Fei; Wang, Shuo; Xu, Mengmeng; Yu, Qianqian; Wang, LinGe
Abstract: Polymersomes (polymeric vesicles) are non-viral delivery vehicles self-assembled from block copolymers (BCPs), holding promising potential in biomedical applications. Despite the higher chemical stabilities of the BCPs, lyophilization is still required for the long-term preservation of the polymersomes and their encapsulated drugs. However, formulation and processing parameters can affect the efficiency of the lyophilization. In this work, we present an approach to evaluate the integrity of polymersomes based on Fluorescence Resonance Energy Transfer (FRET) for rapid optimization of the lyophilization parameters. Specifically, Coumarin 6 (C6) and Nile red (NR)-encapsulated polymersomes were fabricated separately and mixed together for lyophilization. Upon reconstitution, FRET was detected for polymersomes which lost integrity during the lyophilization or reconstitution. The evaluation was carried out for poly(ethylene glycol)- b -poly(lactic acid) (PEG- b -PLA) polymersomes lyophilized with eight different excipients, and the results showed that the best polymersomes integrity could be achieved with the addition of hydroxypropyl-beta-cyclodextrin (HP-β-CD). We believe the approach described here would greatly facilitate the optimization of the polymersomes lyophilization, accelerating the translation of polymersomes to practical applications. Graphical abstract: Image 1 Highlights: Provides an easy-accessible approach to optimize the lyophilization parameters of polymersomes. Assesses polymersomes integrity after lyophilization via FRET-induced fluorescence variation. Successfully evaluated the protective effect of common excipients on PEG- b -PLA polymersomes.